The Abudance Crown of Thorn Starfish (Acanthaster planci) in Coral Reef Ecosystem Tikus Island Bengkulu Province - Tawa, Hasbi; Mulyadi, Aras; Thamrin, Thamrin (Jurnal Perikanan dan Kelautan, 2020)
This research was conducted in June 2019 to determined the abudance crown of thorn starfish (A. planci) and the condition of coral reef in Tikus island. 3 Stations with 2 different depth were taken in Tikus island. The result showed that coral reef from 4 meter depth were in middle-good condition. Percent cover of Station 1 was 44.4%, percent cover of Station 2 was 59.33% and percent cover of Station 3 with 59.04%. Meanwhile, 9 meters depth showed coral reef condition in a bad category 13.93-20.20% using Underwater Photograph Transect method. The abudance crown of thorn starfish (A. planci) in all stations were in normal condition with the highest abudance was 0.004 ind/m2 using Line Intercept Transect method. It means that A. planci hasn’t given a threat for coral reef ecosystem. The abudance of A. planci in each station and 2 different depth also didn’t show any different, based on depth and station.